An Investigation of Differences in Lower Extremity Biomechanics During Single-Leg Landing From Height Using Bionic Shoes and Normal Shoes - Xu, Datao; Zhou, Huiyu; Baker, Julien S.; István, Bíró; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2021)
Bionic shoes using and actual foot shape sole structure can alter the lower limb's biomechanics, which may help in the development of specific training or rehabilitation programs. The purpose of this study was to investigate the biomechanical differences in the lower limb during a single-leg landing task using bionic shoes (BS) and normal shoes (NS). Fifteen healthy male subjects participated in this study, sagittal and frontal plane data were collected during the landing phase (drop landing from 35 cm platform). Our study showed that BS depicted a significantly greater minimum knee flexion angle at initial contact (p = 0.000), a significantly greater minimum (initial contact) hip flexion angle at initial contact (p = 0.009), a significantly smaller sagittal plane total energy dissipation (p = 0.028), a significantly smaller frontal plane total energy dissipation (p = 0.008), a significantly smaller lower limb total energy dissipation (p = 0.017) than NS during the landing phase. SPM analysis revealed that BS depicted a significantly smaller knee joint vertical reaction force during the 13.8-19.8% landing phase (p = 0.01), a significantly smaller anterior tibia shear force during the 14.2-17.5% landing phase (p = 0.024) than NS. BS appear to change the lower limb kinematics at initial contact and then readjust the landing strategies for joint work and joint reaction force, thereby reducing the risk of lower limb skeletal muscle injury. BS have great potential, and future development and application value, which may help athletes to reduce lower limb injury risk.